Development of Community Participation in Preventing Stunting - Yana Sundayani (Politeknik Kesejahteraan Sosial Bandung, 2023)
Participation is participation in an activity by playing an active role to achieve goals with full responsibility. This research aimed to determine the effect of the development of community participation on efforts to prevent stunting. The method used in this study is a survey method with a quantitative approach, and the main tool for collecting data is a questionnaire. The data analysis technique in this study was to use a simple linear regression formula with the help of SPSS 25 for windows. The research location is located in Leuwigoong Village, Leuwigoong District, Garut Regency. The results showed that based on the Anova test with F count 5,747 and a probability significance level of 0.019 <0.05, it can be concluded that the regression model can be used to predict stunting prevention variables. The results of the t test found that t count> t table (2,397 > 1,670), that H0 was rejected statistically significant. Based on the results of the t test, the significant value is less than 0.05 (0.019 <0.05) meaning that there is a significant influence between the development of community participation on stunting prevention.